A qualitative study of the musical thinking and decision making behaviour of Singaporean music students learning to compose - Martin, Jeffrey Alan. (2009)
Music, together with the other arts, is currently accepted as a unique but important way of thinking and knowing. Creativity is regarded as having strong potential for the development of musical knowledge. Although, to a great extent, the justification for including music in general education rests on these assumptions, there is still little research to date investigating the nature of creative thinking in music.